2017
DOI: 10.1590/0100-3984.2016.0076
|View full text |Cite
|
Sign up to set email alerts
|

SPECT/CT with radiolabeled somatostatin analogues in the evaluation of systemic granulomatous infections

Abstract: ObjectiveTo evaluate SPECT/CT with radiolabeled somatostatin analogues (RSAs) in systemic granulomatous infections in comparison with gallium-67 (67Ga) citrate scintigraphy.Materials and MethodsWe studied 28 patients with active systemic granulomatous infections, including tuberculosis, paracoccidioidomycosis, pneumocystosis, cryptococcosis, aspergillosis, leishmaniasis, infectious vasculitis, and an unspecified opportunistic infection. Of the 28 patients, 23 had started specific treatment before the study out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…Our study shows that PET scanning using a somatostatin analogue radioligand can detect pulmonary lesions in patients with active TB. This finding is consistent with a recent case report showing intense DOTANOC uptake in a single mesenteric tuberculous lesion 24 , and several previous nuclear imaging studies using 99mTc- and 111In-labelled somatostatin analogs, that have shown increased uptake in pathological lesions in TB and other granulomatous diseases 20 , 25 27 . However, although we demonstrated that DOTANOC images TB lung disease, there does not appear to be any particular advantage over the standard ligand: the few discrepancies we observed in lesions visualised with the two ligands generally favoured FDG, and lesion uptake was, on average, more than two-fold higher with FDG for individual lesions and for total lung lesions.…”
Section: Discussionsupporting
confidence: 93%
“…Our study shows that PET scanning using a somatostatin analogue radioligand can detect pulmonary lesions in patients with active TB. This finding is consistent with a recent case report showing intense DOTANOC uptake in a single mesenteric tuberculous lesion 24 , and several previous nuclear imaging studies using 99mTc- and 111In-labelled somatostatin analogs, that have shown increased uptake in pathological lesions in TB and other granulomatous diseases 20 , 25 27 . However, although we demonstrated that DOTANOC images TB lung disease, there does not appear to be any particular advantage over the standard ligand: the few discrepancies we observed in lesions visualised with the two ligands generally favoured FDG, and lesion uptake was, on average, more than two-fold higher with FDG for individual lesions and for total lung lesions.…”
Section: Discussionsupporting
confidence: 93%
“…Our results also showed that the specificity of SRI (50%) is quite low as two cases of the infection group showed positive finding on 99m Tc-HYNIC-TOC SPECT/CT, which were misdiagnosed as the culprit tumors of ECS and were then surgically resected. Inflammatory disease demonstrating increased tracer uptake on SRI is not uncommon in the literature because somatostatin receptor is known to be expressed on activated macrophages in inflammatory process (22,23). These findings suggested that SRI may not effectively discriminate tumor-like infectious lesions from ACTH-secreting lung tumors.…”
Section: Discussionmentioning
confidence: 99%
“…DOTATATE PET scan in patients in the USA has shown to have a specificity of 90% for NET 13. However, activated macrophages have been shown to have strong expression of membrane somatostatin receptors,14 and scans with radiolabeled somatostatin analogues are currently being evaluated as a diagnostic technique in patients with infectious granulomatous disease (including TB, leishmaniasis and aspergillosis) in the developing world 15…”
Section: Discussionmentioning
confidence: 99%